2015
DOI: 10.2174/1874155x01509010361
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chord Lengths of Splitter Blades on Performance of Small Axial Flow Fan

Abstract: On the basis of small axial fan with five blades, 6 types of small axial flow fans with different chord lengths splitter blades were designed. Numerical simulation of 6 fan models with splitter blades and prototype fan were done by using Fluent. Based on the obtained simulation results, internal flow characteristics and aerodynamic noise were analyzed and compared. It indicates that: splitter blades with suitable chord length have improved significantly on internal flow characteristics, which inhibits backflow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…Although Figure 5 shows an inclination of 46°, this is due to a subtle curvature present in the blades. The blade thickness has been set at 0.5 mm to optimize the flow, following the guidelines of [4]and [6]. This final design is the result of a process of constant iteration and refinement, aimed at achieving superior performance and outstanding efficiency in the fan's operation.…”
Section: Design Stagementioning
confidence: 99%
See 1 more Smart Citation
“…Although Figure 5 shows an inclination of 46°, this is due to a subtle curvature present in the blades. The blade thickness has been set at 0.5 mm to optimize the flow, following the guidelines of [4]and [6]. This final design is the result of a process of constant iteration and refinement, aimed at achieving superior performance and outstanding efficiency in the fan's operation.…”
Section: Design Stagementioning
confidence: 99%
“…In recent times, there has been a notable increase in the utilization of axial fans for cooling electronic components or heat transfer equipment [1],both in industrial and domestic settings [2], [3], which leads designers to make improvements to them to maximize their performance [4], [5], and reduce the noise they generate [6], [7]. Most of the research is based on improving existing axial fan designs [8], with a concentration on studies involving aerodynamic profile geometry or inlet geometry [9], [10], others study the effects of blade twisting or airfoil [11]- [14],and others studied the behavior of the fluid and its influence on fan noise generation [15], [16].…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al [4] applied the splitter blade to the axial fan and found that splitter blades could improve the static pressure of the axial fan and decrease the pressure pulsation on the surface of the main blades. Further, Li et al [5] investigated the influence of the chord length of splitter blades on the performance of the axial fan and their results showed that splitter blades with an appropriate chord length would have a certain effect on enhancing the static characteristics and improving the aerodynamic noise characteristics. Zhang et al [6] investigated the effects of convex grooves on the blade pressure surface and the wave-shaped trailing edge on the performance of an axial fan.…”
Section: Introductionmentioning
confidence: 99%